DIGITALISASI SISTEM PELAYANAN TERPADU SATU PINTU (PTSP) PADA LAYANAN PENDIDIKAN DI KANTOR KEMENTERIAN AGAMA KABUPATEN MALANG - Maftukhah, Inayatul (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
The rapid development of technology can encourage the government to implement digital public services, for the effectiveness of the service process provided to the community. This is one of the technology utilization carried out by the government, which is called e-government. The focus of this research is to describe the concept of digitizing a one-stop integrated service system (PTSP) in education services and describe the supporting and inhibiting factors of digitizing a one-stop integrated service system (PTSP) in education services at the Office of the Ministry of Religion of Malang Regency. The research method used by researchers is a qualitative method with a descriptive approach. Data collection techniques are observation, interviews and documentation. The data analysis technique is the Miles and Huberman model: Data collection, data reduction, data display, and conclusion drawing/verification. And checking the validity of the data, namely source triangulation and technical triangulation. The results of this study are the concept of digitalization of one-stop integrated services (PTSP) has been implemented by the Malang Regency Office of the Ministry of Religious Affairs, which provides the benefits of fast and easy service processes taking place digitally. Supporting factors are human resources and adequate infrastructure, while inhibiting factors are the lack of competent networks and resources in the institution.